Prevalence of Anaemia in Children of 6 Months to 59 Months in Narayanganj, Bangladesh - Uddin, MK; Sardar, MH; Hossain, MZ; Alam, MM; Bhuya, MF; Uddin, MM; Rahman, MJ (Journal of Dhaka Medical College, 2011)
Objective: To determine the prevalence of anaemia in children of 6 to 59 months old in Narayanganj, Bangladesh to help policy makers to formulate health and nutrition policies in national level. Methods: In 2009, a representative sample of 767 young children (age ranging from 6 to 59 months) had their haemoglobin concentration measured. The sampling process was in three stages: at first, 5 Upazila hospitals, 1 District hospital and a 200 bedded specialized hospital were randomly selected to represent the whole district and its 5 geographic urban and rural areas. Next, using census lists, 15 census sectors were randomly chosen. Finally, 767 children of 6-59 months were selected. Blood was collected by vein puncture and haemoglobin concentration was measured with a haemoglobin meter. Data were analysed to determine prevalence of anaemia. Results: The prevalence of anemia among the children of 5-59 months old was 40.9% for the district as a whole. Prevalence in the municipal region of Narayanganj was 40.9%. The rural areas had the highest prevalence of 66.9%. Prevalence was almost two times higher in children of 6-23 months in comparison to children of 24-59 months i.e. 61.8% and 31.0% respectively. The mean haemoglobin concentrations in the younger and older age groups were 10.4(±1.5) g/ dl and 11.4(±1.4) g/dl respectively. There is no difference found between the sexes. Conclusion: This is the first assessment of anaemia prevalence among young children in Narayangaj, Bangladesh. As there is very high prevalence of anaemia among the children studied in Fatulla upazila, especially those in the age group 6-23 months, public health interventions are needed here most. Key words: Anaemia; iron deficiency anaemia; haemoglobin; child heath; Bangladesh. DOI: 10.3329/jdmc.v19i2.7084 J Dhaka Med Coll. 2010; 19(2) : 126-130